A Review on Cost and Return of Medicinal and Aromatic Plants Cultivation in India - Rathore, Rakesh (International Journal of Economic Plants, 2024)
The purpose of this paper is to review the cost and return of medicinal and aromatic plants cultivation. Relevant and scholarly articles of various researchers were reviewed. The articles were searched using the keywords "medicinal and aromatic plants" along with cost and return, cultivation. Scientific platforms such as Google Scholar and Scopus were searched, along with, annual reports, magazines, newspapers, medicinal plants board websites etc. The reviews compiled collective information on cost and return, benefit cost ratio. Medicinal and aromatic plants provide a higher return compared to traditional crops. However, marketing is an important constraint in cultivation. Understanding the economics of cultivation of medicinal and aromatic plants is an important step in designing future policies. This paper tries to fill the gap and contributes literature on cost and return of cultivation of medicinal and aromatic plants, which may be helpful in improving the linkage of value chain of the sector.